2014
DOI: 10.1590/1809-9823.2014.13117
|View full text |Cite
|
Sign up to set email alerts
|

Escolarização e seus efeitos no letramento de idosos acima de 65 anos

Abstract: ResumoObjetivo: Analisar as condições de letramento de pessoas com idade mínima de 65 anos, comparando tais condições entre idosos que têm grau de instrução compatível com nível superior completo e aqueles que não têm. Métodos: Foram aplicados um questionário e um teste de leitura contendo textos de gêneros diversos a 72 sujeitos idosos residentes na cidade de Curitiba-PR. O questionário contemplou idade, nível de escolarização e práticas atuais de leitura e escrita. No teste de leitura, os sujeitos foram conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…One of these studies mentions the National Indicator of National Literacy -INAF, which, in the last 10 years, has shown through tests and questionnaires applied in residences that a large part of the population has had shallow knowledge of reading, writing and numbers, and hence difficulties in understanding texts, calculations and logical reasoning 2 . Others studies 3,4 have shown that Brazil still has readers and writers who present difficulties in interpretation and textual production of secondary genres. These studies also show that the implementation of a literacy work from the practice of various genres, among the population that is within and outside the academic environment, is a prerequisite for people to have an improvement in their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies mentions the National Indicator of National Literacy -INAF, which, in the last 10 years, has shown through tests and questionnaires applied in residences that a large part of the population has had shallow knowledge of reading, writing and numbers, and hence difficulties in understanding texts, calculations and logical reasoning 2 . Others studies 3,4 have shown that Brazil still has readers and writers who present difficulties in interpretation and textual production of secondary genres. These studies also show that the implementation of a literacy work from the practice of various genres, among the population that is within and outside the academic environment, is a prerequisite for people to have an improvement in their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…No último censo da população brasileira, a taxa de analfabetismo de pessoas idosas alcançou o valor de 26,2% [15]. Os resultados encontrados [18][19][20][21][22] vieram de encontro com este estudo quando categoricamente 47,5% dos entrevistados possuíam ensino fundamental incompleto. Essa taxa quando comparada com outros estudos brasileiros foi coincidente.…”
Section: Discussionunclassified
“…Um estudo realizado em Curitiba-PR demonstrou que, independentemente do nível de escolaridade das pessoas idosas, há utilização restrita das práticas relacionadas à linguagem escrita, uma vez que tanto aqueles que possuíam formação superior quanto os que não possuíam tiveram dificuldades em interpretar informações simples de textos. Dessa maneira, fica claro que o grau de escolaridade não garante o processo de letramento (20) .…”
Section: Discussionunclassified